Penggunaan Video Cerita Rakyat “Asal Usul Cikaputrian” sebagai Alternatif Bahan Ajar Menulis Karangan Narasi Kelas V - Kosmilia, Utami; Widjojoko, Widjojoko; Wardana, Deni (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Indonesian language learning in elementary schools is an education that is useful for improving students’ skills in understanding and using good language as a communication tool in oral or written form in everyday life. This era of globalization has brought developments in technology and interesting information for learning namely video. So researchers are interested in analyzing the intrinsic elements of the “Asal Usul Cikaputrian” video as an alternative teaching material for writing narrative essays. This study uses a qualitative approach and content analysis methods. The research subject is the intrinsic element contained in the dialogue “Asal Usul Cikaputrian”. The aims of this research are: (1) to describe the intrinsic elements obtained in the video of “Asal Usul Cikaputrian” folklore video (2) to describe teaching materials for writing narrative essays from the analysis of the intrinsic elements of “Asal Usul Cikaputrian” folklore video. Therefore, when teachers use teaching material in the process of learning activities to make it easier for students to understand and achieve learning success. The teaching materials were obtained from the results of the intrinsic elements analysis of the video entitled “Asal Usul Cikaputrian” from Banten. The intrinsic elements studied by the researcher are theme, character, plot, point of view, and mandate. Through alternative teaching materials for writing narrative essays for fifth-grade elementary school students, teachers can apply these teaching materials in fifth-grade elementary school, by applying these teaching materials to be able to make it easier to master material designwhen conducting learning creativity to write narrative essays for more innovative learning.